Role of alloying elements in vanadium-based binary alloy membranes for hydrogen separation - Lee, Young-Su; Ouyang, Chuying; Suh, Jin-Yoo; Fleury, Eric; Cho, Young Whan; Shim, Jae-Hyeok (ELSEVIER SCIENCE BV, 2012)
We investigate the metal-hydrogen interaction in vanadium alloyed with X = Fe, Ni, Al, Ti, and Nb using first-principles calculations. The site energy of interstitial hydrogen depends on both the volume and the presence of a nearby alloying element; the two effects are analyzed separately. The effective volume of the alloying element follows the sequence Nb > Ti > Al > V > Ni > Fe, and a larger volume lowers the site energy on average. Locally, Al appears to be the strongest hydrogen repellent, and Ti exhibits the strongest affinity for hydrogen. The original tetrahedral coordination by the metal atoms is also affected and the effect is the most pronounced in Ni, where the hydrogen atom in the octahedral interstitial site is strongly stabilized. A 16-atom body centered cubic special quasi-random structure is utilized to obtain the statistical distribution of site energies in V12X4. The obtained site energies at 673 K have the following sequence: Ti < Nb < Al < Ni < Fe. This result indicates that the strongest local repulsion brought by Al is not necessarily correlated to the largest drop in solubility due to the compensation by the elastic effect. The strong repulsion, however, would cause a pronounced decrease in the configurational entropy. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: PERMEATION CHARACTERISTICS; THERMODYNAMIC PROPERTIES; DIFFUSION; NIOBIUM; ABSORPTION; TANTALUM; SYSTEM; PHASE